Challenges in diagnosing nasopharyngeal tumors - Alexandru Aristide Alexe; Mihai Victor Lupascu; Haldun Septar; Anca Pantea Stoian; Andra Iulia Suceveanu; Viorel Gherghina; Iuliana Cindea; Alina Doina Nicoara; Laura Mazilu; Razvan Hainarosie; Felix Voinea; Adrian Paul Suceveanu (Journal of Mind and Medical Sciences)
Malignant nasopharyngeal tumors account for approximately 4% of ENT malignant tumor pathology and 1% of all cancers. The diagnosis of nasopharyngeal tumors is often late, the reason being the location in a silent anatomical region in terms of symptomatology and accessibility. Thus, approximately 70% of newly diagnosed patients with nasopharyngeal carcinoma unfortunately present with the condition in an advanced local stage. The early signs and symptoms are varied (nasal obstruction, hearing loss, otalgia, headache) and are usually ignored by the patient and even by the doctor in the initial stage of nasopharyngeal tumor evolution. Approximately 5% of patients have systemic metastases at presentation, the most common location being bone. Latent Epstein-Barr virus infection appears to be involved in the pathogenesis of nasopharyngeal carcinoma. There is no exact evidence of how often a nasopharynx tumor’s first sign is unilateral hearing loss. Thus, further work is required to determine that exactly to help patients get diagnosed faster and therefore improving their therapeutical options. This study aims to explore which symptoms are most common as the first indication of NPC, as well as how these symptoms compare to each other in terms of frequency and likelihood of occurrence.